Transforming Engagement, Happiness and Well-Being Enthusing People, Teams and Nations - Scott-Jackson, William (Springer International Publishing, 2018)
This book aims to help leaders maximise the engagement of employees and citizens by exploring the impact of a process of active enthusiasm (PACE). Engagement of employees has long been recognised as a key factor for organisational and national success. Yet, worldwide, engagement levels languish at only 25%. Providing a practical model, developed from in-depth global research, the authors show that engagement is continuous and cannot be assessed by annual surveys. Instead it demonstrates that it is specific to individuals and will only increase if employee perceptions are improved. Readers will discover how the PACE process model can be used to maximise employee engagement through the modification of primary causal factors, and consequently generate direct outputs such as increased productivity and reduced absenteeism. Transforming Engagement and Wellbeing provides an invaluable set of tools to help leaders enthuse their people and to improve individuals' optimism and propensity for engagement, making it essential reading for academics interested in human resource management, as well as managers, leaders and policy-makers.